March's advanced organic chemistry : reactions, mechanisms, and structure. - Smith, Michael, 1946 October 17- (Wiley, 2013)
Seventh Edition integrates advances in organic chemistry and reactions into acclaimed text "Who can hope to be seriously accepted as a member of the organic chemistry community without being in possession of at least one edition of March?"--Chemistry & Industry, from a review of the Sixth Edition Now in its seventh edition, March's Advanced Organic Chemistry remains the gold standard in organic chemistry, setting the foundation for organic chemistry theory and practice. Throughout its many editions, readers have relied on its clear, carefully written descriptions of reactions, mechanisms, and structure to plan and execute multi-step synthetic reactions. Offering a comprehensive treatment of organic chemistry, the text explores: Structure of organic compounds, explaining important organic chemistry bonds, fundamental principles of conformation, stereochemistry of organic molecules, and reactive intermediates Principles of mechanisms in organic chemistry, including acids and bases, photochemistry, sonochemistry, microwave irradiation, and the relationship between structure and reactivity Nature, scope, and mechanisms of individual organic reactions This Seventh Edition updates the text to reflect the most recent advances in organic chemistry and organic reactions. More than 5,500 references have been added to guide students to the latest primary, secondary, and review literature. In addition, there's a literature guide to help readers conduct thorough searches of any topic in organic chemistry. With detailed descriptions of organic reactions to guide students through all the stages of planning and performing multi-step synthetic reactions, March's continues to be the textbook of choice for organic chemistry instructors and students around the world.